2015
DOI: 10.1111/bor.12152
|View full text |Cite
|
Sign up to set email alerts
|

Late Quaternary loess deposition in the southern Chaiwopu Basin of the northern Chinese Tian Shan foreland and its palaeoclimatic implications

Abstract: The piedmont aeolian sediment in Central Asia is has been widely used for Quaternary palaeoclimatic reconstructions. Here we present detailed sedimentological and rock magnetic investigations on 188 samples from the~9.4m-thick Urumqi River section (URS) in the southern Chaiwopu Basin of the northern Chinese Tian Shan foreland. Optically stimulated luminescence (OSL) dating constrains the time-span of the URS loess sedimentation from c. 28 to c. 6.8 ka. This chronology implies that the onset of the URS loess se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Under the cold climatic conditions, the strengthened westerly wind brings more original dust to the deposition area, and the local material contribution decreases, so that χ lf would be higher. Therefore, as well as detrital dust, the Ili loess is also influenced by local materials, and the mixture of different materials weakens the impact on χ fd or χ fd % in the Ili loess and loess in other regions, such as the loess sediments in northern piedmont of Tianshan Mountains (Lu et al, ; H. Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the cold climatic conditions, the strengthened westerly wind brings more original dust to the deposition area, and the local material contribution decreases, so that χ lf would be higher. Therefore, as well as detrital dust, the Ili loess is also influenced by local materials, and the mixture of different materials weakens the impact on χ fd or χ fd % in the Ili loess and loess in other regions, such as the loess sediments in northern piedmont of Tianshan Mountains (Lu et al, ; H. Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The climate during the late Cenozoic in the Tian Shan and its surrounding area was characterized by a trend of aridification (Sun et al., 2008). In the present studied area, sedimentological and rock magnetic studies on loess sediments have revealed the gradually intensified aridity of the climate since the latest Pleistocene (Lu et al., 2016). The present‐day regional climate is controlled largely by the mid‐latitude westerlies.…”
Section: Geological Geomorphological and Climatic Settingsmentioning
confidence: 76%
“…Weakly‐cemented Paleogene‐Neogene sedimentary strata are mainly exposed in the proximal foreland basin owing to folding and thrusting (Lu, Burbank, Li, et al., 2010, 2015) (Figure 1b), and a small amount of these strata are exposed sporadically in some small, uplifted intermountain basins (Deng et al., 2000; Jolivet et al., 2018). Late Quaternary alluvial deposits and aeolian loess often uncomfortably overlie the pre‐Quaternary strata involved in thrust‐related folds (Lu, Burbank, & Li, 2010, 2016).…”
Section: Geological Geomorphological and Climatic Settingsmentioning
confidence: 99%
“…As for terrace T 5 , an ESR sample taken from the layer of silt at the top of terrace gravels was dated to 142 ± 14 ka (Lu et al., 2014). This age is obviously older than the OSL age of 27.4 ± 3.1 ka of the sample taken from the base of loess covering the deposits of terrace T 5 (Lu et al., 2016), likely implying that the loess has not accumulated immediately after terrace abandonment. Given the uncertainty of the dates, we do not determine the time interval between terrace abandonment and loess deposition.…”
Section: Alluvial Sequencesmentioning
confidence: 87%